English Education Master Students' Self-Regulated Learning Strategies in Academic Writing - Wijaya, Kristian Florensio (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2021)
English Education Master Students’ Self-Regulated Learning Strategies in Academic Writing Kristian Florensio Wijaya Sanata Dharma University, Yogyakarta kristianwijaya500@gmail.com Abstract There is a propensity for language teachers to handicap graduate students as independent, competent and strategic academic writers. Therefore, it is easier to discover graduate students struggling intensely to produce and publish qualified academic writing products to targeted journal articles. Due to this ubiquitous fact, self-regulated learning strategies need to be entrenched potently within L2 academic writers to enable them to become more mindful, resourcefulness, autonomous, and proficient academicians who excel in their subject-specific fields. This was a small-scale qualitative study implementing qualitative content analysis to obtain a more obvious portrayal regarding some specific phenomena taken place in one particular circumstance. To fulfill this objectivity, two research instruments were utilized in this study namely the Likert-scale Questionnaire and interview protocols to maintain the robustness of the data gathering processes. 15 English Education Master Students together with 3 selected interviewees were also invited to fill out the questionnaire and participate in the interview activities. In line with the gathered data, the qualitative results revealed that the majority of English Education Master Students have transformed into more life-long and proficient academic L2 writers for they continuously showed greater resilience, efforts, commitment to accomplish various academic writing projects. Keywords: Self-regulated learning strategies, academic writing, qualitative content analysis, academic L2 writers